2009
DOI: 10.2746/095777309x477159
|View full text |Cite
|
Sign up to set email alerts
|

Transpalpebral enucleation using a chain écraseur

Abstract: Summary This study was undertaken to describe the technique, complications and outcome of the use of a chain écraseur for transpalpebral enucleation in horses under general anaesthesia. We report its use in 53 horses, reviewing the subject details, reasons for enucleation, surgical technique, intra‐ and post operative complications, and long‐term outcome. Intraoperative complications included mild to moderate bleeding in 4 horses. Post operative complications included mild periorbital post operative swelling i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 3 publications
1
7
0
Order By: Relevance
“…The rate of complications in this study was similar to previous studies and confirms the relative safety of enucleation compared to other surgical procedures. Contrary to a previous report , orbital implants were not significantly associated with post‐enucleation complications in this study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The rate of complications in this study was similar to previous studies and confirms the relative safety of enucleation compared to other surgical procedures. Contrary to a previous report , orbital implants were not significantly associated with post‐enucleation complications in this study.…”
Section: Discussionsupporting
confidence: 90%
“…Horses that have suffered with an intractably painful eye are assumed to have an improved quality of life following enucleation and it has been shown that horses are able to return to a variety of occupations following unilateral enucleation . Despite this, owners of horses with diseased eyes are often reluctant to consider enucleation .…”
Section: Introductionmentioning
confidence: 99%
“…Five studies described complications during the recovery period associated to ocular surgery [375][376][377][378][379]. For these procedures, horses were at higher risk of unsatisfactory recoveries compared to horses undergoing splint bone excision [375].…”
Section: Other Factorsmentioning
confidence: 99%
“…Launois et al (2009) had good success reducing equine enucleation surgical complications with a feedback-controlled bipolar electrocautery device. García-López et al (2009) adapted an instrument to remove uterine polyps to mechanically achieve orbital haemostasis and optic nerve transection in enucleation procedures in horses, but seemed to have a few more surgical complications related to experience using the instrument.…”
Section: E Brooksmentioning
confidence: 99%
“…The subconjunctival approach is thought to be quicker and associated with less haemorrhage, but risks leaving behind some secreting tissues (Brooks 2006). The specific details of both techniques are described in the accompanying articles by Launois et al (2009) and García-López et al (2009).…”
mentioning
confidence: 99%